THE UNIQUENESS OF MODERN RUSSIAN-LANGUAGE LITERATURE IN UZBEKISTAN (Educator Insights: Journal of Teaching Theory and Practice, 2025)
Modern Russian poetry in Uzbekistan has its own history, rich heritage and strong traditions. Russian-language literature in Uzbekistan is a unique phenomenon reflecting the versatility of the country's cultural landscape. It has a number of features that distinguish it from the literature of other regions.